1983
DOI: 10.1152/jappl.1983.55.6.1916
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat stress on exercise-induced changes in regional blood flow in sheep

Abstract: Radioactive microspheres were used to measure cardiac output and blood flow to most major tissues in sheep at rest and during treadmill exercise (3- to 6-fold increase in metabolic rate for 30 min) in thermoneutral (TN) [dry bulb temperature (Tdb) = 16 degrees C, wet bulb temperature (Twb) = 12 degrees C] and mildly hot (MH) (Tdb = 40 degrees C, Twb = 23 degrees C) environments. During exercise, rectal temperature increased more under MH than under TN conditions; exercise-induced changes in the major central c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
3

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 21 publications
3
35
3
Order By: Relevance
“…Microsphere injections into the femoral artery and jugular vein, together with blood sampling from the pulmonary artery, enabled the calculation of the proportion of femoral blood flow passing through arteriovenous anastomoses (Hales, Fawcett & Bennett, 1978). It is unlikely that microsphere migration of any relevance to the present study would have occurred, since (a) monitoring radioactivity levels in the ear and lungs of rabbits for an 8 week period indicated no relocation of microspheres (Hales & Cliff, 1977), and (b) as previously discussed (Bell, Hales, King & Fawcett, 1983), no consistent trend was found in the blood flow values of any tissues of sheep subjected to three exercise periods at 48 h intervals.…”
Section: Experimental Protocolmentioning
confidence: 58%
“…Microsphere injections into the femoral artery and jugular vein, together with blood sampling from the pulmonary artery, enabled the calculation of the proportion of femoral blood flow passing through arteriovenous anastomoses (Hales, Fawcett & Bennett, 1978). It is unlikely that microsphere migration of any relevance to the present study would have occurred, since (a) monitoring radioactivity levels in the ear and lungs of rabbits for an 8 week period indicated no relocation of microspheres (Hales & Cliff, 1977), and (b) as previously discussed (Bell, Hales, King & Fawcett, 1983), no consistent trend was found in the blood flow values of any tissues of sheep subjected to three exercise periods at 48 h intervals.…”
Section: Experimental Protocolmentioning
confidence: 58%
“…Previous studies in humans (Kirwan et al 1987;Nielsen et al 1990Nielsen et al , 1993Nielsen et al , 1997, rats (Laughlin & Armstrong, 1983) and miniature swine (Armstrong et al 1987;McKirnan et al 1989) have shown that blood flow to active muscles is either maintained or increased when heat stress is superimposed during exercise. This is in contrast to the significant reductions in blood flow to some exercising muscles found in sheep with heat stress (Bell et al 1983). …”
Section: Discussionmentioning
confidence: 74%
“…apparently greater than the pre-treatment activity of 200 IU/l), which was not present in sheep that walked for up to 3 h, without voluntarily stopping, no adverse consequences of the exercise treatment were found. Although exercise affected physiological variables in a predictable manner (Bell et al, 1983), the heart rate of the sheep at this speed of walking did not exceed 160 beats/min, the respiration rate was below 85 breaths/min, there was no evidence of dehydration (as determined by plasma osmolality) or hyperthermia (the rectal temperature of the sheep did not increase by more than 0.68C during exercise, and remained below 408C for most sheep). Therefore, a treatment regime of walking on a treadmill at 0.5 m/s at zero grade for up to 5 h or until a decrease in performance was observed was used in a replicated study.…”
Section: Treadmillmentioning
confidence: 86%